Ecological aspects of solid domestic wastes influence on agricultural landscapes - Молчанова, А. В. (Scientific Progress & Innovations, 2017)
Number of consumer goods and increases of solid domestic wastes are one of the biggest environmental problems. The rate of increase in the volume of solid domestic wastes in excess of global trends Ukraine exceed in 2–3 times and it is 10 % or more. In Ukraine there are at least 160 thousand ha of lands occupied by landfills, it is one of the highest accumulation of wastes in the world, equipment inspection and improvement areas occupied by landfills missing. Warehousing and storage of waste is burning issue, so bulk waste is recycled in Ukraine, and the consequences are environmental pollution (soil, water, air), worsening health.